The inclusive process of the deaf and hearing impaired: a search in the review (Research, Society and Development, 2021)
This is a literature review of a narrative nature, based on a broad discussion of thematic-scientific production. The same consisted of a qualitative research, using a bibliographic investigation of narrative character carried out through consultation in online research databases: Scielo, ERIC and academic Google. In an analysis of the achievements within the scope of inclusion regarding the guarantee of rights for Deaf or hearing impaired subjects, the laws of Brazil have ensured these individuals, as citizens and civil members of this society, the total right to enjoy them, either them in the educational sphere or in their social life. Bringing to policy, unfortunately, the educational policy for the deaf in Brazil, which aims to ensure that deaf students complete regular education on an equal footing with deaf and Portuguese-speaking students, does not fully work in practice. The need to know the dynamics of Libras in different teaching modalities is of paramount importance to mount strategies to combat the non-literacy of students with deafness, prejudice and the creation of means to improve the education and quality of life of deaf people.